Ashes and fibers used in the elaboration of ecological concrete: a literary review - Coronel Sánchez, Yan Carlos (2022)
New construction technologies and materials are currently applied more frequently in the search for quality improvements, considering the environmental and economic aspects of construction. The objective of the article is to carry out a systematic review on the use of ashes and fibers for the elaboration of ecological concrete.  56 indexed articles were reviewed with a publication age of 7 years, from 2015 to 2021, which are distributed in the following databases 21 articles in Scopus, 4 in EBSCO host, 9 in Scielo, 6 in Proquest, and 16 ScienceDirect, in which the use of ashes such as rice husk, sugar cane bagasse, fly ash, and fibers such as banana bark, sawdust, steel, glass, polypropylene, rubber, and granulated rubber. In conclusion, it was possible to verify that there are alternatives that allow the production of sustainable materials and/or products using ashes and fibers, which are of great importance, since they have outstanding characteristics, such as being strong, light, economic and ecological, while it was evidenced that ashes and fibers influence the strength of concrete ranging from 231 to 700 kg/cm2.